Electricity: it's use in the home - Romick, Minnie Louisa (My University, 1894)
Introduction: The word electricity is derived from the Greek word—electron, the name for, amber, which when rubbed with a dry wooden cloth, attracted light bodies of every kind, such as a small piece of paper, gold leaf, etc. It is strange that, a power so rich in its resources, so universal in its application, and so readily controlled, as electricity was not earlier introduced into the home. Although electricity is sometimes an enemy greatly to be feared, because of its being pregnant with danger, it is most frequently man’s obedient servant easily controlled by the will and a powerful auxiliary in the noblest enterprises that aid most in civilization. It carries messages by means of telegraphic wires from the cities in each states and country to the most distant limits of the globe. It promises to lessen the toil of workman by lending an inexhaustible mechanical power. We find in fact that the adoption of electrical apparatus in house-keeping, is gradually becoming more widespread, making some things more useful and others more ornamental, until in the near future we may anticipate its presence in the home will be indispensable.
Citation: Romick, Minnie Louisa. Electricity: it's use in the home. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Electricity; Home; Light; Electron; Interior design; Theses; Manuscripts (documents)